The educator's guide to linguistics - Gordon, Tatiana (Emerald Publishing Limited : Information Age Publishing, Inc., 2012)
This book provides an accessible and reader-friendly overview of linguistic research. The meaning of complex linguistic concepts is illuminated with the help of engaging stories, analogies, and graphics. The book brings theoretical discussion to life by citing familiar bits of language such as names of popular business establishments, recognizable song lyrics, and famous adages. These examples taken from day-to-day life ultimately help students recognize the language in their own environment as worthy of observation and analysis.Above all, the book is meant to help future teachers in the classroom. It is this goal that largely determines its scope. The text provides an overview of those studies that have relevance to classroom practice. For instance, the chapter on neurolinguistics covers research into the gestures that accompany speech, and the chapter on semantics places special emphasis on discussing the role of conceptual metaphors in cognition. Each of the book's eleven chapters concludes with a section entitled "Implications for Instruction." These sections engage the reader in exploring the practical significance of linguistic research.